An epidemiological study to assess the determinants influencing decision of medical termination of pregnancy among women undergoing medical termination of pregnancy in maternity homes, in a metropolitan city - Chakkarwar, Priyanka P.; Fernandes, Sophia D. (International Journal Of Community Medicine And Public Health, 2018)
Background: Unwanted pregnancy alone does not determine the decision to terminate pregnancy but a combination of factors influence each other to terminate pregnancy. This study was undertaken to know about the reasons for undergoing MTP. AIM: “An epidemiological study to assess the determinants influencing decision of medical termination of pregnancy among women undergoing medical termination of pregnancy in maternity homes, in a metropolitan city.” Methods: Cross sectional study was conducted from December 2013 to December 2015. The study area was the maternity homes under Municipal Corporation. Women in the age group 19-49 years undergoing MTP, who gave consent were included in the study. Women in the age group <18 years undergoing MTP and women not in a state to participate in the study were excluded from study. The sample size for study was 199. Data was collected using semi structured validated questionnaire and analysed using IBM SPSS Version 21.0 statistical software. Association between variables was analysed using Chi-square test, Fisher’s exact test. Results: All study subjects were married women. The mean age of the women undergoing MTP was 28.41 years. Illiteracy among wife and husband was (09.11%) and (10.55%) respectively. 54 (27.14%) subjects belonged to upper-lower socioeconomic class. The most common 123 (61.81%) reason for undergoing MTP was “completed family”, followed by “medical reason”. Conclusions: Study results emphasize the need to encourage women for the use of FP methods.